Gaming disorder among adolescent in Indonesia: A multi-settings cross-sectional study - Satria, Budi; Mustanir, Mustanir; Oktari, Rina Suryani; Marthoenis, Marthoenis (Acta Biomedica Atenei Parmensis, 2024)
Background and aim of the work: The escalating phenomenon of online gaming among adolescents has emerged as a notable concern, exerting profound effects on their individual lives and interpersonal dynamics. The adolescents' struggle to effectively manage their emotional responses has been implicated in a spectrum of school-related disturbances. This study aims to investigate the prevalence of gaming disorder among adolescent in Indonesia.Research design and methods: This cross-sectional study was conducted among adolescents in the city of Banda Aceh in Indonesia. A multistage random sampling method was used to select 616 students from six junior high schools across the city. The presence of Internet gaming disorder was accessed using the Indonesian version Internet Gaming Disorder Scale-Short Form (IGDS9-SF). Descriptive statistics were used to analyze the data.Results: It was found that 30.8% of the adolescents had already experienced a gaming disorder. The mean score was 18.25 (SD = 6.773) and the subscales including preoccupation (Mean 2.43, SD=1.025), withdrawal (Mean. 1.88. SD=1.251), tolerance (Mean.2.42. SD=1.331), persistent (Mean.2.20. SD=1.323), displacement (Mean.1.74. SD=1.200), problem (Mean.1.83.SD=1.170), deception (Mean.1.55. SD=1.016), escape (Mean.2.68. SD=1.437), and conflict (Mean.1.52. SD=1.031).Conclusions: The prevalence of gaming disorder was relatively high among Indonesia adolescents. The high prevalence rate and high average scores indicate the need for stronger prevention and intervention programs to overcome gaming disorder. Comprehensive attention, particularly in schools, is necessary, along with preventive measures to reduce gaming disorder.